A Two - Phase Distributed Reconfiguration Algorithm for Node Failures in IP-Over-WDM Networks - Sreenath, N.; Palanisamy, Balaji (International Conference on Systems and Networks Communications : October 29-November 3, 2006, Tahiti, French Polynesia, 2006)
In Wavelength Routed Wavelength Division Multiplexing (WR-WDM) networks, a set of lightpaths (all-optical communication paths) defines the virtual topology. Internet Protocol (IP) makes use of virtual topology to route its traffic in the optical form. In the event of a node failure, the virtual topology may be partitioned so that a set of nodes may not be able to communicate with another set of nodes. The failure may also affect the objective function value leading to decreased network performance. In such a case, it may be indispensable that the connectivity in the virtual topology is restored and the network performance is improved in terms of objective function value. Hence, it may be necessary to alter the existing virtual topology. Altering of a virtual topology is called as virtual topology reconfiguration. In this paper, we propose a two-phase distributed algorithm for virtual topology reconfiguration in the event of a node failure. The algorithm restores the failed connectivity during phase I. Phase II of the algorithm improves the network performance by bringing down the objective function value of the network.